Origin of transversal displacement of the plasma flux moving in a curvilinear magnetic field - Timoshenko, A.I. (Вопросы атомной науки и техники, 2008)
It is shown that transversal displacement of the plasma flux propagating across toroidal magnetic field, may be interpreted as a result of conversion (by means of Lorentz force) of the energy obtained by electrons in a field of polarization force and in a field of forces aroused due to magnetic field curvature, into kinetic energy of the transversal movement of the plasma as a whole. The same interpretation is valid also for the drift motion of a single particle. Показано, що поперечне зміщення плазмового потоку може бути інтерпретовано як результат перетворення (за допомогою сили Лоренца) енергії, отриманої електронами в полі поляризаційної сили і в полі сил, пов'язаних з кривизною магнітного поля, в кінетичну енергію поперечного руху всієї плазми. Така ж інтерпретація справедлива і для дрейфового руху окремої частинки. Показано, что поперечное смещение плазменного потока может быть интерпретировано как результат преобразования (посредством силы Лоренца) энергии, полученной электронами в поле поляризационной силы и в поле сил, связанных с кривизной магнитного поля, в кинетическую энергию поперечного движения всей плазмы. Такая же интерпретация справедлива и для дрейфового движения отдельной частицы.